Analysis of Promotion Strategy in Building Branding and Product Sales - Nadila, Nidya; Sukmarini, Andi Vita; Mujahid, Mujahid (Newinera Publisher, 2023)
This study aims to determine and analyze promotional strategies in building branding and product sales in the Rumah Catering culinary business located in Gowa Regency, South Sulawesi Province. The research method used is descriptive qualitative with data collection through in-depth interviews, observation and document study. The results showed that there are four promotional strategies out of five promotional strategies used or implemented by Rumah Catering, namely direct marketing, advertising, personal selling and sales promotion. Meanwhile, publicity/public relations has not been implemented by Rumah Catering. The main inhibiting factors affecting the implementation of all promotional strategies are the insufficient number of marketing personnel and limited budget and location coverage. In addition, the supporting factors that contribute to the success of promotional strategies at Rumah Catering are advertising and promotion, consumer readiness to buy products and the presence of competitors. This study provides input and recommendations for Rumah Catering culinary businesses to consider developing a more optimal promotional strategy in overcoming obstacles and utilizing existing supporting factors.